Acute Effects of Delta-9-Tetrahydrocannabinol on Performance Monitoring in Healthy Volunteers - Spronk, Desiree; Dumont, Glenn J.; Verkes, Robbert J.; de Bruijn, Ellen R. (Frontiers in Behavioral Neuroscience, 2011)
Rationale: The error-related negativity (ERN) is a negative event-related potential that occurs immediately after an erroneous response and is thought to reflect human performance monitoring. Delta-9-Tetrahydrocannabinol (THC) administration in healthy volunteers has been linked to impaired performance monitoring in behavioral studies, but to date no studies have examined the effects of cannabinoids on the ERN. Methods: EEG data from 10 healthy volunteers was recorded during execution of a speeded choice reaction time task (Flankers task) after administration of THC or placebo vapor in a double-blind randomized crossover design. Results: The findings of this study show that the ERN was significantly reduced after administration of THC. The behavioral outcomes on the Flankers task showed no indications of drug-induced impairments. Discussion: The diminished ERN reflects impairments in the process of performance monitoring. The task design was not optimized to find behavioral effects. The study shows that cannabinoids impair performance monitoring.